2007
DOI: 10.1007/s10549-007-9757-7
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor B (PRB) promoter hypermethylation in sporadic breast cancer

Abstract: The majority of tumours were methylated for PRB. This did not directly compromise PRB expression suggesting that other factors may down regulate the PR gene. When PRB was expressed, it correlated with good prognostic markers and better overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…These results correlate closely with biochemical ligand binding assays and clinical response rates to endocrine therapy 53,54. Furthermore, PR promoter methylation is commonly observed in primary breast cancer cases and may be a mechanism by which this protein is downregulated 55. Importantly, higher PR levels are negatively correlated with tumor size and grade.…”
Section: Introductionsupporting
confidence: 73%
“…These results correlate closely with biochemical ligand binding assays and clinical response rates to endocrine therapy 53,54. Furthermore, PR promoter methylation is commonly observed in primary breast cancer cases and may be a mechanism by which this protein is downregulated 55. Importantly, higher PR levels are negatively correlated with tumor size and grade.…”
Section: Introductionsupporting
confidence: 73%
“…Similar results were found by Feng et al (27); however, Gaudet et al reported that PRB (but not PRA ) methylation was a frequent event (92.2%), although the actual levels of methylation were weak (18). Furthermore, another group reports higher frequency of PRB methylation in sporadic breast tumors (26). It should be noted that inconsistency of reported methylation frequencies could be partly due to different sensitivities of methods used for measuring methylation, highlighting the need for standardized assays.…”
Section: Discussionmentioning
confidence: 99%
“…The position of the primers within PRA and PRB genes are shown in Figure 1. The PRB CpG sites have been previously analyzed by others and were found to be associated with expression (25, 26). We found high concordance in methylation between adjacent sites and we therefore used mean values from all pyrosequenced CpG sites as a measure of methylation of a given gene.…”
Section: Methodsmentioning
confidence: 99%
“…Cytosine methylation of DNA at cytosine-guanine dinucleotides and post-translational modifications of histones (including acetylation and methylation) are part of an epigenetic regulatory system that controls the establishment of permissive or repressive chromatin structure. There is increasing evidence, stemming mainly from studies in breast and endometrial cancers, that the expression of PRs can be regulated by certain epigenetic events within the PR gene (Lapidus et al, 1996;Ferguson et al, 1998;Sasaki et al, 2001Sasaki et al, , 2002Sasaki et al, , 2003Liu et al, 2003;Xu et al, 2004;Xiong et al, 2005;Wu et al, 2006;Mc Cormack et al, 2008;Gaudet et al, 2009). Xiong et al (2005) reported that hypermethylation of the PR-B promoter silenced its gene expression in adenocarcinoma cells, which could be restored through DNA demethylation in conjunction with histone acetylation.…”
Section: Introductionmentioning
confidence: 99%